2017
DOI: 10.1177/0033688217716505
|View full text |Cite
|
Sign up to set email alerts
|

Concept Based Instruction: Enhancing Grammar Competence in L2 Learners

Abstract: Over the past decades, much of the discussion regarding grammar teaching has evolved around the identification of the best language teaching approach to facilitate effective learning of English language among second language (L2) learners. Despite the various approaches introduced and implemented in the realm of L2 teaching, the language performances of these learners are still ‘off-target’ as they are still found not able to use the correct language expressions to serve their communicative needs. Investigatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Thai study also revealed that in spite of being able to have access in all tenses comfortably, students' low confidence leads them to be unsure to tense selection [37]. This finding was supported by [33] stating that the students of UiTM Kuantan Campus always have problems in understanding the concepts and rules of grammar tenses. Even though some students claimed that the grammar difficulties often troubled them in learning grammar tenses, they could survive and had good performance at grammar tenses.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Thai study also revealed that in spite of being able to have access in all tenses comfortably, students' low confidence leads them to be unsure to tense selection [37]. This finding was supported by [33] stating that the students of UiTM Kuantan Campus always have problems in understanding the concepts and rules of grammar tenses. Even though some students claimed that the grammar difficulties often troubled them in learning grammar tenses, they could survive and had good performance at grammar tenses.…”
Section: Discussionmentioning
confidence: 84%
“…Traditional grammar instruction, such as that of Audio-Lingual or PPP (Present-Practice-Production) views language learning as learning about the structure or grammar rules of the target language [33]. Moreover, rules are not modified or replaced in the course of acquisition; instead, new rules whose properties may be contradictory or incompatible with other rules are simply added [31].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, another finding also came to the similar result showing no a significant relationship between any of the four cheating classifications or professional misconduct and the characteristics of grade point average, gender, or level of parent's education (Winrow, Reitmaier-Koehler, & Winrow, 2015). Another report suggested that consciousness of the penalties toward academic dishonesty, including plagiarism, would certainly prevent cheating students (Guraya & Guraya, 2018). The recent studies deal with how the students engaged with the cheating deeds and exposed which gender was involved in cheating deeds more serious, revealed the causes of the cheating, their motives of cheating, and the media used to cheat.…”
Section: Introductionmentioning
confidence: 85%
“…Quantitative approach for descriptive was used dealing with this research (Creswell, 2014;Fauziati, 2017). The setting of the research was in one of universities located in Tanjung Pinang, Riau Archipelago, Indonesia.…”
Section: Methodsmentioning
confidence: 99%